Structural Path Analysis: Applications to Structural Changes in the Andalusian economy (1990-1999) - M. Carmen Lima Díaz; Manuel Alejandro Cardenete Flores; José Vallés Ferrer (European Regional Science Association (ERSA), 2003)
Social Accounting Matrices (SAM) are an useful tool that enables to get extenser information than Input-Output analysis as far as they work not only with an economy's intersectorial relations, but also with consumers' behaviour, government or foreign sector; reflecting the income flow of rent. In this paper, we use Social Accounting Matrices for Andalusia for years 1990, 1995 y 1999, that we got from previous works. With this information we use "path analysis" technique to obtain the main changes in the productive structure and demand in Andalusia for the last ten years. Those changes will be represented in a three-dimensional picture. We also want to know which are the sectors that have strongly contributed to regional economic growth. Finally we measure the influence of sectorial shocks on themselves and also on the other sectors of this regional economy. Keywords: social accounting matrix, regional accounting, structural analysis. JEL: C67, D57, R15.
Keywords: 330